2009
DOI: 10.1177/0960327109102798
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induced by morphine in brain of rats fed with a protein deficient diet

Abstract: The objective of the study is to determine the damage by oxidative stress induced by morphine in brain of rats fed with a protein-deficient diet. Twenty-eight malnourished male Wistar rats, 30 days old, were used in the study. The animals were divided into four groups of 7 rats per group. Group I received NaCl and the groups II; III and IV intraperitoneally received 3, 6 and 12 mg/kg of morphine sulphate, respectively, in a single dose. Animals were sacrificed and the levels of glutathione (GSH), dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The pathway enrichment analysis identified an oxidative stress-related pathway as being modulated by morphine exposure, in agreement with previous studies [ 11 , 48 , 49 , 50 ]. Oxidative stress is an abnormal physiological process and is defined as “an imbalance between antioxidants and oxidants, resulting in the disruption of redox signaling and the corresponding molecular damage” [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…The pathway enrichment analysis identified an oxidative stress-related pathway as being modulated by morphine exposure, in agreement with previous studies [ 11 , 48 , 49 , 50 ]. Oxidative stress is an abnormal physiological process and is defined as “an imbalance between antioxidants and oxidants, resulting in the disruption of redox signaling and the corresponding molecular damage” [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…Morphine induces reactive oxygen species formation in various brain cells (Xu et al,2006). In addition, opiates acutely decrease glutathione levels within the brain (Goudas et al,1999; Guzman et al,2006; Calderon‐Guzman et al,2009) and suppresses glutathione peroxidase activity (Xu et al,2006). Repetitive hypoxic episodes may have also played a role; however, lower glutathione levels are more likely with chronic hypoxia (Raman et al,2005).…”
Section: Discussionmentioning
confidence: 99%
“…This effect coincides with previous studies carried out in our laboratory where the products of lipoperoxidation were found to reduce in the cerebrum after the sibutramine treatment, especially in female rats. This suggests that the effect could be attributable to the chemical structure of sibutramine which possesses certain functional groups like dimethylamine and chlorine heteroatom all found in the aromatic ring which confers to them electrophilic character that facilitates their interaction with lipidic structure of the cerebrum (Calderon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%